2021
DOI: 10.7250/9789934225901
|View full text |Cite
|
Sign up to set email alerts
|

Nodokļu plānošana Latvijā un starptautiskā vidē. Mācību grāmata

Abstract: Grāmatas mērķis ir palīdzēt izprast nodokļu piemērošanu gan vietējā, gan starptautiskā vidē. Tā sniedz ieskatu nodokļu plānošanā, ietverot nodokļu teoriju un praktiskos jautājumus. Grāmata studentiem mācībām studiju programmā «Muitas un nodokļu administrēšana». Grāmatā apskatīta arī Latvijā esošā nodokļu sistēma, kas balstīta uz spēkā esošo normatīvo aktu regulējumu 2020. gada 1. janvārī. Ņemot vērā, ka normatīvie akti tiek regulāri mainīti, grāmatā nodokļu izpratnes vajadzībām doti vispārīgi piemēri, lai izp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Balatsky, evaluating the results of calculations using his methodology, pointed out that with the three-parameter method, Laffer points "are either absent or have unrealistic values", and with the two-parameter method, they "improbably jump over the years." 132 E. Balatsky and N. Ekimova, analysing similar approaches of I. Ananiashvili, V. Papava 133 and G. Loladze 134 concluded that all their approaches were based on the methodology of static functions, which led to serious computational difficulties and very questionable estimates, which results in either overestimated or underestimated fiscal parameters. 135 At the same time, the works in which Balatsky tried to describe the connection of the Laffer curve with the tax base had been already published by him in 1997.…”
Section: Third Groupmentioning
confidence: 99%
“…Balatsky, evaluating the results of calculations using his methodology, pointed out that with the three-parameter method, Laffer points "are either absent or have unrealistic values", and with the two-parameter method, they "improbably jump over the years." 132 E. Balatsky and N. Ekimova, analysing similar approaches of I. Ananiashvili, V. Papava 133 and G. Loladze 134 concluded that all their approaches were based on the methodology of static functions, which led to serious computational difficulties and very questionable estimates, which results in either overestimated or underestimated fiscal parameters. 135 At the same time, the works in which Balatsky tried to describe the connection of the Laffer curve with the tax base had been already published by him in 1997.…”
Section: Third Groupmentioning
confidence: 99%